Resolusi Konflik Internasional: Studi Kasus Konflik Bersenjata Sipil antara Sudan Armed Forces (SAF) dan Rapid Support Force (RSF) di Sudan - Rendi Prayuda; Riski Syafrana; Rio Sundari; M. Arsy Ash Shiddiqy (Andalas Journal of International Studies (AJIS), 2024)
Sudan is located in the Sahel â€œCoup Beltâ€ region, which has a long history of coups and military rule in Africa. Tensions peaked on April 15, 2023 when Rapid Support Force (RSF) paramilitary forces led by Mohamed Hamdan â€œHemedtiâ€ Dagalo and Sudan Armed Forces (SAF) forces loyal to General Fattah al-Burhan fought in the capital region, Khartoum. This paper aims to analyze the conflict resolution of civil armed conflict between SAF and RSF in Sudan. This paper uses a qualitative method with documentation studies as a source of research information. The results of this study indicate that there are conflict resolution efforts that have been made to achieve peace in the country of Sudan. By using Johan Galtung's conflict resolution approach, three forms of resolution models have been grouped, namely Peacemaking with the help of IGAD (Intergovernmental Authority on Development), AU (African Union), Saudi Arabia and the United States, Peacekeeping with the help of the UN Security Council mandate namely UNITAMS United Nations Integrated Transition Assistance Mission in Sudan) and Peacebuilding by forming three framework agreements namely the Juba Peace Agreement (JPA), the Treaty of Jeddah and the Sudan Framework.